2010
DOI: 10.1002/polb.22185
|View full text |Cite
|
Sign up to set email alerts
|

Polymer segmental dynamics and solvent thermal transitions in poly(ethyl acrylate)/p‐xylene mixtures

Abstract: A poly(ethyl acrylate) polymer network was swollen with different concentrations of the nonpolar solvent p‐xylene, cpx, from xerogel until saturation (0 ≤ cpx ≤ 0.85). Differential scanning calorimetry (DSC) and thermally stimulated depolarization currents (TSDC) techniques were employed to study the polymer segmental dynamics and the solvent thermal transitions in homogeneous (cpx < 0.20) and partially crystallized (cpx ≥ 0.20) PEA/p‐xylene mixtures. Our DSC measurements indicate that p‐xylene undergoes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 45 publications
3
17
0
1
Order By: Relevance
“…Dielectric studies on such systems do not suffer from solvent relaxations, dc conductivity and interfacial polarization masking the polymeric dipolar relaxations in hydrogels. In agreement with the phase diagram of the system, constructed on the basis of DSC and TSDC data,131 the mixtures can be classified into three qualitatively different groups, each one corresponding to different solvent content, c px, region. More specifically, for p ‐xylene contents c px < 0.20, the mixtures are homogeneous in the whole temperature range studied and the polymer is monotonously and strongly plasticized.…”
Section: Perspectivesmentioning
confidence: 73%
See 4 more Smart Citations
“…Dielectric studies on such systems do not suffer from solvent relaxations, dc conductivity and interfacial polarization masking the polymeric dipolar relaxations in hydrogels. In agreement with the phase diagram of the system, constructed on the basis of DSC and TSDC data,131 the mixtures can be classified into three qualitatively different groups, each one corresponding to different solvent content, c px, region. More specifically, for p ‐xylene contents c px < 0.20, the mixtures are homogeneous in the whole temperature range studied and the polymer is monotonously and strongly plasticized.…”
Section: Perspectivesmentioning
confidence: 73%
“…Of particular interest are partially crystallized mixtures, including as a prominent category the polymer/water mixtures, that is, polymer/solvent mixtures, where the polymer component does not spontaneously crystallize, whereas the thermodynamics allows the phase separation and crystallization of the solvent. Interestingly, DSC results indicated that the phase diagram of a polymer mixture with a non‐polar solvent can be similar to those of hydrogels 131. Figure 16 shows results from a work in progress, the Arrhenius plot of the α process in cross‐linked PEA swollen in p ‐xylene in wide ranges of composition, based on DRS and TDSC data.…”
Section: Perspectivesmentioning
confidence: 93%
See 3 more Smart Citations